Names of central labour organisations in Spain
016a-0059-001 Names of Central Labour Organisations in Spain. Union General de Trabajadores ( U.G.T ). Headquarters moved during rebellion from Madrid to Valencia. Affiliated to I.F.T.U. Membership small in Catalonia. Confederacion Nacional de Trabajadores ( C.N.T ). Headquarters in Barcelona. Nearly half the membership in Catalonia. Called Anarcho-syndicalists, and groups large majority of Catalan proletariat. Affiliated to International Association of Workers ( A.I.T ), of anarcho-syndicalist tendency. Iberian Anarchist Federation ( F.A.I ). Possesses organisations throughout the whole of Spain, but influence chiefly felt in Catalonia, where it practically controls larger part of the C.N.T. Unified Socialist Party of Catalonia ( P.S.U.C ), formed as result of events in July, 1936, by fusion of:- Socialist Union of Catalonia (a purely Catalan Socialist Party); Socialist Party, Catalan section (2nd International); Catalan Workers' Party (the former proletarian tendency in the Esquerra - see E.R.C. below); Catalan Communist Party (3rd International). Workers' Party of Marxist Unification ( P.O.U.M. ) Founded at end of 1935 by fusion of Peasant Workers' Party, Joaquim Maurin's party, and the Spanish Communist Left directed by Andres Nin. Workers Federation of Trade-Union Unity ( F.O.U.S. ) Membership 70,000. Influenced by P.O.U.M. Group of autonomous Trade Unions fighting for Trade Union unity. Esquerra Republicana Catalana ( E.R.C. ) The Left Party of republican petty bourgeoisie, founded by Macia. In possession of the Catalan Generalidad since bourgeois revolution of April 1931. Catalan Action ( A.C. ) The Party of the republican bourgeoisie. Politically, to the right of the Esquerra. Union of "Rabaissaires" ( U.R. ) a corporative union of Catalan farmers under the influence of the Esquerra and the P.O.U.M. WJB/MT. 3.3.37. 292/946/16a/60